Teaching primary physical education - Lawrence, Julia Clare; Sage eBooks (London : SAGE, 2012)
Physical education is an important part of the primary curriculum and one that provides unique challenges for those involved with its teaching. This book provides a concise overview of the knowledge, skills and understanding required for the confident teaching of physical education in primary schools.
Specialized.
Description based on print version record.
Keywords: Physical education for children -- Great Britain; Elementary school teaching -- Great Britain; Electronic books